Student Metacognition in Mathematics Problem Solving on Set Materials: Metakognisi Siswa dalam Pemecahan Masalah Matematika pada Materi Himpunan - Shodikin, Ali; Nurkumala, Silvia Eka; Sumarno, Wahyu Kyestiati (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2022)
Solving mathematical problems is an important thing in mathematics. Solving narrative problems requires complex thinking skills, namely cognitive skills and understanding of using the right methods or tactics. Awareness of students in using their thoughts to plan, control, and assess their cognitive processes and tactics is the meaning of metacognition. This research is a descriptive study that aims to describe the level of students' metacognition in solving mathematical problems, especially a set of material. The population in this study is class VII B of SMPN 2 Sukodadi. To focus on data analysis, 3 students were closed who represented problem-solving abilities, they are high, medium, and low. Based on the data analysis conducted by researchers, the subject who has a high level of mathematical problem-solving ability is included in the "reflective use" metacognition level. The subject who has a moderate level of mathematical problem-solving ability is included in the "strategic use" metacognition level, and a subject who has a low level of problem-solving ability in math problems is classified as “aware use” metacognition level.  From these results, it is recommended for teachers to pay attention to the tendency of students' metacognition levels based on students' problem solving levels, both in planning, learning processes and assessment in order to realize differentiated learning.